INFORMATION ON THE SIZE AND OTHER QUANTITIES OF Λ-ORBITALS IN HYPERNUCLEI FROM EXPERIMENTAL Λ-ENERGIES - Grypeos, M. E.; Koutroulos, C. G.; Petridou, Th. A. (HNPS Advances in Nuclear Physics, 2019)
An approach is proposed on the basis of which the experimentally known two lower energy eigenvalues of a Λ- particle assumed to be bound in a hypernucleus by a central potential (from a fairly wide class of them) are able to provide in certain cases rather direct information on estimates of other useful quantities, such as the r.m.s. radii of the Λ Orbitals, kinetic energies, etc. In addition two basic inequalities relating the ground-state mean square radius of the orbit of a particle in a central potential and its kinetic energy, respectively, to the spacing of the two lowest energy levels ΔΕ are investigated and further discussed in connection with the Λ-hypernuclei.